FOREWORD (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
The twenty-first issue of Palimpsest includes research articles, review and professional papers by authors affiliated with prominent universities and research centres in North Macedonia, Slovenia, Slovakia, Albania, Türkiye, Azerbaijan, and Indonesia. Across five thematic sections devoted to linguistics, literary studies, cultural studies, and language teaching methodology, this issue brings together diverse national scholarly traditions and methodological approaches within the philological and cultural research. The papers, written in several languages such as Macedonian, English, Italian, Turkish, and French—cover a broad spectrum of topics, ranging from folklore motifs in literature and analyses of the latest works by contemporary authors to investigations of emerging linguistic phenomena influenced by digitalization, innovative approaches to foreign language teaching, the reception of world literary classics in the fashion industry, and many other subjects. The participation of nearly forty authors and co-authors is in itself a testament to the richness and diversity of the content featured in this issue of Palimpsest.